Impact of unhealthy food/drink marketing exposure to children in New Zealand: A systematic narrative review - Frost H; Te Morenga L; MacKay S; McKerchar C; Egli V (Oxford University Press, 2025)
Unhealthy food and drink marketing exposure to children is known to influence children's dietary choices and the World Health Organization recommends governments protect children from the marketing of unhealthy commodities. This study aims to explore and synthesize children's unhealthy food and drink marketing exposure in New Zealand. A systematic search strategy was undertaken following the PRISMA guidelines. Eight databases were searched for studies from inception to January 2024 on marketing exposure of unhealthy food and drink to children aged 2-17 years. A deductive coding analysis was used, with codes sourced from a modified coding framework developed using a diagram sourced from the ASEAN and UNICEF (2023) report. The diagram demonstrates the pathway from marketing exposure to unhealthy food- and drink-related diseases. A total of 1019 studies were screened for eligibility. Forty-five studies met the inclusion criteria - five qualitative, 34 quantitative and four mixed-method studies. The results are presented in a narrative review format. Findings demonstrated children's exposure to unhealthy food/drink marketing is ubiquitous with clear links to dietary preference and consumption. To improve child health now and over the life course, unhealthy food/drink marketing needs to be subjected to greater restriction with enforceable legislation to protect children from exposure to unhealthy marketing, breaking the chain from exposure to ill health.
Keywords: advertising; marketing; unhealthy food and drink